2014
DOI: 10.1016/j.ijid.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and virological characteristics of hepatitis B virus in HIV-infected individuals in Sudan

Abstract: In HBV/HIV co-infected Sudanese patients, the ratio of genotype A to non-A was higher than that in mono-infected patients. The genotype E intra-group divergence in HBV/HIV co-infected individuals was significantly higher than that in HBV mono-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 51 publications
4
35
1
Order By: Relevance
“…Baseline HBV DNA levels in HBsAg‐positive participants were comparable to those in HBsAg‐negative participants, although higher levels of VBT occurred in the HBsAg‐negative group. These findings confirm previous calls for the need for nucleic acid testing to detect HBV infection, particularly in high‐risk populations, such as HIV‐positive individuals receiving lamivudine . Clinical consequences of undetected HBV infection include increased risk of HCC.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Baseline HBV DNA levels in HBsAg‐positive participants were comparable to those in HBsAg‐negative participants, although higher levels of VBT occurred in the HBsAg‐negative group. These findings confirm previous calls for the need for nucleic acid testing to detect HBV infection, particularly in high‐risk populations, such as HIV‐positive individuals receiving lamivudine . Clinical consequences of undetected HBV infection include increased risk of HCC.…”
Section: Discussionsupporting
confidence: 86%
“…These findings confirm previous calls for the need for nucleic acid testing to detect HBV infection, particularly in high-risk populations, such as HIV-positive individuals receiving lamivudine. 9,10,25,40 Clinical consequences of undetected HBV infection include increased risk of HCC. Although lamivudine is still being used in some African countries, including Ethiopia, 12 the findings of the present study further support the need to replace lamivudine with tenofovir to treat HBV/HIV coinfected individuals.…”
Section: Occult and False Occult Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the observed prevalence is slightly lower than the 6.9 and 9.8% reported in Yaoundé, Cameroon and Khartoum, Sudan respectively [12, 19]. It should be noted however that the prevalence of OBI is dependent on the sensitivity of the DNA assay used, demography and the population studied [7].…”
Section: Discussionmentioning
confidence: 91%
“…A molecular study involving multiple countries in West Africa found preS2 deletions in 30.6% (33/108), including 15/35 (42.8%) from Nigeria with unknown HIV status [18]. Other studies including patients from SSA or with GTE have reported lower frequencies of preS2 deletions, and the effect of HIV infection on the presence of these mutations in this region is unclear [29,32,41,42]. In this study, preS2 indel mutations were associated with baseline liver fibrosis severity, but not fibrosis regression; liver fibrosis information was not available for the GTE patients in the prior studies.…”
Section: Discussionmentioning
confidence: 99%